Wound repair and immune function in the Pseudomonas infected CF lung: before and after highly effective modulator therapy - Matthews, Emma Lea; Hirsch, Meghan June; Prokopczuk, Federico; Jones, Luke I.; Martínez, Eriel; Barnes, Jarrod W.; Krick, Stefanie (Frontiers in Cellular and Infection Microbiology, 2025)
The leading cause of death for people with cystic fibrosis (pwCF) continues to be due to respiratory-related illnesses. Both wound repair and immune cell responses are dysregulated in the CF airways, creating a cycle of unresolved injury and perpetuating inflammation. PwCF are predisposed to colonization and infections with opportunistic bacteria like Pseudomonas aeruginosa (Pa), the most common adult pathogen in CF. Pa possesses key virulence factors that can exacerbate chronic inflammation and lung injury. With the approval of highly effective modulator therapies like elexacaftor/tezacaftor/ivacaftor (ETI), pwCF eligible for ETI have seen drastic improvements in lung function and clinical outcomes, including an increased life expectancy. While modulator therapies are improving bronchial epithelial cellular processes in wound repair and some areas of immunity, many of these processes do not reach a non-CF baseline state or have not been thoroughly studied. The effect of modulator therapy on Pa may lead to a reduction in infection, but in more longitudinal studies, there is not always eradication of Pa, and colonization and infection frequency can return to pre-modulator levels over time. Finally, in this review we explore the current state of additional treatments for CF lung disease, independent of CFTR genotype, including anti-inflammatories, phage-therapies, and Pa vaccines.